2017
DOI: 10.3892/mmr.2017.6104
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA expression signature and the therapeutic effect of the microRNA-21 antagomir in hypertrophic scarring

Abstract: Hypertrophic scars (HS) area fibroproliferative disorder of the skin, which causes aesthetic and functional impairment. However, the molecular pathogenesis of this disease remains largely unknown and currently no efficient treatment exists. MicroRNAs (miRNAs) are involved in a variety of pathophysiological processes, however the role of miRNAs in HS development remains unclear. To investigate the miRNA expression signature of HS, microarray analysis was performed and 152 miRNAs were observed to be differential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…Microarray analysis revealed that at least 152 miRNAs were altered in the expression of HTS, including 82 upregulated miRNAs and 70 downregulated miRNAs. High expression of miRNA downregulated the core proteoglycan expression to promote hyperplasia of fibrous scar tissue (Guo et al, ). It was reported miR‐21 was upregulated, and the expression level was 5.5l times higher than that in normal skin tissue.…”
Section: The Epigenetic Mechanism Regulating the Formation Of Myofibrmentioning
confidence: 99%
“…Microarray analysis revealed that at least 152 miRNAs were altered in the expression of HTS, including 82 upregulated miRNAs and 70 downregulated miRNAs. High expression of miRNA downregulated the core proteoglycan expression to promote hyperplasia of fibrous scar tissue (Guo et al, ). It was reported miR‐21 was upregulated, and the expression level was 5.5l times higher than that in normal skin tissue.…”
Section: The Epigenetic Mechanism Regulating the Formation Of Myofibrmentioning
confidence: 99%
“…The tissue under the experimental wounds were injected with 100 µl of solution containing 10 nM miR-495 agomir (one side) or control (the other side). The injections were carried out on days 5 and 10 after wounding [30]. After recording was the initial area of the wound, the size of the wound was recorded regularly, as was the time required for wound healing.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, miRNAs are characterized by dynamic changes during embryonic development and usually suppress expression of factors in foetal wounds 99 . In Table 2, we present a summary of research primarily focused on the impact of miRNAs in scar formation during the adult stage 100‐120 . Differentially expressed miRNAs have been detected between scar lesions in adult versus embryonic skin 36,121 .…”
Section: Involvement Of Diverse Moleculesmentioning
confidence: 99%